General Principles of Law at the Turn of Civilisations - Brodecki, Zbigniew; Konopacka, Magdalena (Polish Review of International and European Law, 2023)
This review of general principles of law at the process of great changes observed in reality shows not only the past that have been (diversity of the view; contentious issues) and the present (impulse to merge; impetus for thinking) but also the future. The aim of this synthesis was to reconstruct the system of general principles of international law (the need to take into account the general principles of private law and the general principles of law constructed in the process of regional integration of states) as well as the vision of future work on this issue aimed at muted understanding and cooperation for mutual benefit.